Turning on photoelectric activity by cation exchange within an anionic pyrene-based hydrogen-bonded organic framework. (September 2022) - Qin, Jian-Hua; Xiao, Zhi; Zhang, Ji-Rui; Ren, Shu-Xian; Hu, Yu-Xin; Yang, Xiao-Gang; Ma, Lu-Fang; Li, Dong-Sheng
Abstract: The assembly of hydrogen-bonded organic frameworks (HOFs) has been proposed as robust porous materials for gas storage/separation, catalysis, molecular recognition, optical applications, enzyme encapsulation, and so on. However, efficient way to obtain well-organized HOFs still remains challenge. Herein, a novel of anionic pyrene-based HOF [BMI]2 [H2 TBAPy] was synthesised under ionothermal conditions. Relationship between the arrangement of photoactive 1, 3, 6, 8-tetrakis ( p -benzoic acid) pyrene molecules and photophysical properties were well studied by the combination of experiments and density functional theory. Through a facile cation-exchange process, the encapsulation of D–π–A dye cations into the HOF nanochannels could sinificantly broaden its light-harvesting region to NIR. The integrated composite can turn on photoelectric activity of the title HOF owing to strong dipole–dipole interactions and efficient energy transfer between host–guest. Graphical abstract: A novel of anionic pyrene-based HOF was synthesised under ionothermal conditions. Through a facile a cation-exchange process, a D–π–A dye cations encapsulated host-guest system shows sinificantly photoelectric activity "turn-on" owing to the strong dipole–dipole interactions between the dye cation and the anionic framework. Image 1 Highlights: One anionic pyrene-based hydrogen-bonded organic framework (HOF) [BMI]2 [H2 TBAPy] was synthesised under ionothermal conditions. The encapsulation of D–π–A dye cations into the HOF nanochannels could sinificantly broaden its light-harvesting region to NIR. The integrated composite can turn on photoelectric activity of the title HOF owing to strong dipole–dipole interactions and efficient energy transfer between host–guest.